Optimizing Utilization of Hazardous Waste and Biomass as Solid Fuel for Co-Firing - Fandy Ahmad Fauzy; Etih Hartati; Dyah Marganingrum (Universitas Diponegoro, 2023)
Continuously high use of fossil fuels may lead scarcity of these energy sources in the future. Therefore, it is necessary to develop renewable energy to ensure its availability. One of the efforts in the development of renewable energy and the aims of this study is to examine the utilization Fly Ash (FA), Bottom Ash (BA) combined biomass sludge of Wastewater Treatment Plant (WWTP) and municipal solid waste) materials as an alternative energy source (briquette raw materials) for co-firing in textile industry boilers. Briquettes were made with a composition of 60% FABA and 40% biomass which were then varied in composition. The parameters measured were proximate, calorific value, and shatter index. The feasibility test of briquettes was carried out using a Tanner diagram, where all briquettes made can be burned as fuel. Optimum briquettes quality was measured based on the criteria according to the Minister of Environment and Forestry Regulation No. 06/2021. The results showed that the composition of three briquettes that had optimum quality and met the criteria were briquettes with composition 10%FA:50%BA:40%Biomass (variation of WWTP sludge and biomass) with a calorific value and sulfur content of 3,578 Kcal/kg and 0,70%; 3,890 Kcal/kg and 0,82%; and 3,864 Kcal/kg and 0,96%.